Introduction to scholastic theology - Leinsle, Ulrich Gottfried (Catholic University of America Press, 2010)
There are a number of overviews of scholastic philosophy in print, all of which focus either on one stream of thought, one denomination, or one time period. With this book, distinguished historian of philosophy Ulrich Leinsle offers the first comprehensive introduction to scholastic theology a textbook for both Protestant and Catholic students.